Serum osteocalcin and carboxyterminal propeptide of type I procollagen in rheumatoid arthritis. Issue 5 (May 1993) - Kröger, H; Risteli, J; Risteli, L; Penttilä, I; Alhava, E
Abstract : OBJECTIVES--Previous reports indicate that serum osteocalcin (serum bone GLA protein (S-BGP)) and carboxyterminal propeptide of type I procollagen (PICP) can be used as indicators of bone formation and turnover. The purpose of this study was to assess the activity of bone formation in patients with rheumatoid arthritis (RA) using S-BGP and S-PICP. The biochemical data were compared with data obtained from bone histomorphometry. METHODS--Concentrations of S-BGP and S-PICP were measured in 119 women with RA aged 30-66 years and 47 healthy female controls matched for age. Bone histomorphometry of iliac crest samples was performed in 107 patients with RA. RESULTS--Weak to moderate correlations between the serum markers and histological bone formation parameters were found. Concentrations of S-BGP and S-PICP were significantly decreased in patients with RA compared with the controls (S-BGP 7.2 (2.3) v 8.7 (2.1) micrograms/l; S-PICP 105 (32) v 117 (38) micrograms/l. The lowest values were found in patients with recent onset RA. CONCLUSIONS--These findings suggest that bone formation and bone remodelling are generally reduced in patients with RA.